Genetic Analysis of The Leptin Gene in Goats Based on GenBank DNA Sequences - Amrullah, Muhammad Fajar; Utomo, Budi; Utama, Suzanita; Suprayogi, Tri Wahyu; Lestari, Tita Damayanti; Restiadi, Tjuk Imam; Belgania, Ristaqul Husna (Universitas Airlangga, 2023)
The Leptin gene is the gene that produces the leptin hormone, which is released from adipose tissue and can increase the productivity of animals. This study aimed to identify polymorphic nucleotides, changes in amino acid components, and species of goats based on GenBank Leptin DNA sequence data. A total of five goat leptin DNA sequences were extracted from NCBI GenBank data. The leptin DNA sequence was aligned with Bioedit to locate SNPs and amino acid changes. The tree produces cultivars grown using Clustal Omega Ver. 1.2.4. Based on the DNA sequencing results of leptin genes in five goats, five SNPs were located in the coding sequence (CDS), SNPs g.17T/A, g.43T/A, g.74G/A, g.93C/A. and d. 386A/G. SNP was a missense mutation and a silent mutation. The analysis of phylogenetic trees of Leptin showed that there were three breeds of goats in one branch and two breeds of goats in different branches. These results provided the first report for further studies on the genetic diversity of leptin genes in different local goat breeds.